Designing the Article 6.4 mechanism Assessing selected baseline approaches and their implications - Lo Re, Luca (OECD/IEA Climate Change Expert Group Papers, 2019)
Different options of methodological approaches for setting emission baselines are currently under consideration in the international climate negotiations. This paper examines options for baseline approaches for the Article 6.4 mechanism, and draws lessons from how baselines have been used for other market mechanisms. The paper highlights that the different approaches being discussed offer advantages and disadvantages in the context of Article 6.4. Moreover, the paper points out that a one size- fits-all approach to setting baselines is unlikely to be appropriate for the new mechanism, given the variety of possible mitigation activity types and contexts. In particular, analysis of Clean Development Mechanism projects shows that a single baseline approach led to wide variations in baseline levels, implying the need to revise some methodologies if they are to be applied to Article 6.4. The paper also discusses benefits and implications for host Parties participating in the Article 6.4 mechanism, which may affect how Parties achieve their NDCs